2008
DOI: 10.15288/jsad.2008.69.430
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trajectories of Substance Use From Early to Late Adolescence: A Comparison of Rural and Urban Youth

Abstract: Objective-This study investigated differences in the development of heavy drinking and marijuana use among students in urban and rural areas and assessed whether any such differences can be accounted for by locality differences in racial/ethnic makeup, social disorganization/low social bonding, feelings of despondency and escapism, and the availability of drugs.Method-Drawn from 62 South Dakota middle schools involved in a drug prevention field trial, participating students were assigned to a locality category… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 23 publications
2
61
0
1
Order By: Relevance
“…Research spanning the past 20 years has consistently suggested that substance use in rural communities is a serious problem (Atav & Spencer, 2002;Briddell, 2009;Edwards, 1992;Johnston, O'Malley, Bachman, & Schulenberg, 2005;Shears, Edwards, & Stanley, 2006;Wright & Neeraja, 2005). Researchers have also found that heavy drinking increases at a faster rate among rural adolescents when compared to urban adolescents (Martino, Ellickson, & McCaffrey, 2008). Atav and Spencer (2002) found that rural students were at significantly higher risk for substance use and other disruptive behavior (e.g., carrying weapons) than suburban and urban adolescents.…”
Section: Rurality and Latino=a Substance Usementioning
confidence: 99%
“…Research spanning the past 20 years has consistently suggested that substance use in rural communities is a serious problem (Atav & Spencer, 2002;Briddell, 2009;Edwards, 1992;Johnston, O'Malley, Bachman, & Schulenberg, 2005;Shears, Edwards, & Stanley, 2006;Wright & Neeraja, 2005). Researchers have also found that heavy drinking increases at a faster rate among rural adolescents when compared to urban adolescents (Martino, Ellickson, & McCaffrey, 2008). Atav and Spencer (2002) found that rural students were at significantly higher risk for substance use and other disruptive behavior (e.g., carrying weapons) than suburban and urban adolescents.…”
Section: Rurality and Latino=a Substance Usementioning
confidence: 99%
“…This methodology was applied in multiple research areas and distinct trajectories were described in relation to http://dx.doi.org/10.1016/j.drugalcdep.2014.08.020 0376-8716/© 2014 Elsevier Ireland Ltd. All rights reserved. alcohol use Schulenberg et al, 1996), smoking (Brook et al, 2008(Brook et al, , 2007Hu et al, 2008;Ingvar Rosendahl et al, 2008;Lessov-Schlaggar et al, 2008), drug use in general and joint use of multiple drugs Martino et al, 2008;Orlando et al, 2005;Wanner et al, 2006), and aggression, delinquency or social withdrawal (Broidy et al, 2003;Cjte et al, 2002;Huang et al, 2011;Lacourse et al, 2002Lacourse et al, , 2003Oh et al, 2008;Prendergast et al, 2010;Tremblay et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although most adolescents' substance use does not progress to abuse or dependence, approximately 11% of U.S. adolescents meet the criteria for a substance use disorder (Winters, Leittne, Wagnger, & O'Leary Tevyaw, 2007). Urban youth are particularly vulnerable to early use and future abuse of illicit drugs and alcohol (Martino, Ellickson, McCaffrey, 2008). Adolescents who live in metropolitan areas are more likely than those in nonmetropolitan areas to use marijuana and alcohol during the past year (Johnston et al, 2009).…”
Section: Introductionmentioning
confidence: 99%